2022
DOI: 10.3390/ijms232113228
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Treatment with Allogenic Mesenchymal Stem Cells of a Healthy Donor on Peripheral Blood Mononuclear Cells of Patients with Severe Alopecia Areata: Targeting Dysregulated T Cells and the Acquisition of Immunotolerance

Abstract: Alopecia areata (AA) is an autoimmune condition related to the collapse of the immune privilege of hair follicles. Certain AA populations present severe clinical manifestations, such as total scalp hair or body hair loss and a treatment refractory property. The aim of this study was to assess the effects of allogenic human mesenchymal stem cells (hMSCs) from healthy donors on the peripheral blood mononuclear cells (PBMCs) of severe AA patients, with a focus on the change in the cell fraction of Th1, Th17, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that severe AA is due to hair loss caused by the attack of immune cells on the hair follicles. 8 , 20 Therefore, early identification and intervention may be able to effectively prevent the incidence of severe AA. We obtained 2483 IGs from ImmPort database, and 706 resting CD4 memory T cells-related genes, 291 neutrophils-related genes, 26 gamma delta T cells-related genes and 90 mast cells-related genes from the MSigDB database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that severe AA is due to hair loss caused by the attack of immune cells on the hair follicles. 8 , 20 Therefore, early identification and intervention may be able to effectively prevent the incidence of severe AA. We obtained 2483 IGs from ImmPort database, and 706 resting CD4 memory T cells-related genes, 291 neutrophils-related genes, 26 gamma delta T cells-related genes and 90 mast cells-related genes from the MSigDB database.…”
Section: Resultsmentioning
confidence: 99%
“…However, the current clinical treatment methods for severe AA are limited, and combined immunosuppressive therapy is often required, but its adverse reactions are relatively large, and the recurrence rate after drug withdrawal is high, so it is not the first choice for AA treatment. 8 Therefore, it is particularly important to identify and intervene early in AA patients who may progress to severe AA, which will help improve the incidence of severe AA and its prognosis.…”
Section: Introductionmentioning
confidence: 99%